2017
DOI: 10.1016/j.ympev.2016.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Global phylogeography of Oithona similis s.l. (Crustacea, Copepoda, Oithonidae) – A cosmopolitan plankton species or a complex of cryptic lineages?

Abstract: 14Traditionally, many small-sized copepod species are considered to be widespread, bipolar or 15 cosmopolitan. However, these large-scale distribution patterns need to be re-examined in 16 view of increasing evidence of cryptic and pseudo-cryptic speciation in pelagic copepods. 17Here, we present a phylogeographic study of Oithona similis s.l. populations from the Arctic Introduction 34The existence of widespread or cosmopolitan species is widely accepted in marine plankton 35 due to the lack of apparent geog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 90 publications
(9 reference statements)
3
49
0
Order By: Relevance
“…The study of pelagic copepod populations at the molecular level helps to identify environmental factors that drive the appearance and fixation of adaptive traits. Current approaches applied to pelagic copepods typically use ribosomal genes, mitochondrial cytochrome oxidase subunit I and II genes and microsatellites markers to identify species, genotypes and haplotypes (e.g., Blanco‐Bercial, Álvarez‐Marqués, & Bucklin, ; Blanco‐Bercial, Cornils, Copley, & Bucklin, ; Cornils, Wend‐Heckmann, & Held, ; Goetze, Andrews, Peijnenburg, Portner, & Norton, ; Hirai, Kuriyama, Ichikawa, Hidaka, & Tsuda, ). With appropriate sampling, the calculation of within‐ and between‐population genetic distances can then be used to infer copepod population structure and connectivity (Kozol, Blanco‐Bercial, & Bucklin, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study of pelagic copepod populations at the molecular level helps to identify environmental factors that drive the appearance and fixation of adaptive traits. Current approaches applied to pelagic copepods typically use ribosomal genes, mitochondrial cytochrome oxidase subunit I and II genes and microsatellites markers to identify species, genotypes and haplotypes (e.g., Blanco‐Bercial, Álvarez‐Marqués, & Bucklin, ; Blanco‐Bercial, Cornils, Copley, & Bucklin, ; Cornils, Wend‐Heckmann, & Held, ; Goetze, Andrews, Peijnenburg, Portner, & Norton, ; Hirai, Kuriyama, Ichikawa, Hidaka, & Tsuda, ). With appropriate sampling, the calculation of within‐ and between‐population genetic distances can then be used to infer copepod population structure and connectivity (Kozol, Blanco‐Bercial, & Bucklin, ).…”
Section: Introductionmentioning
confidence: 99%
“…Oithona similis has been identified from all oceans and climate zones (Razouls, de Bovée, Kouwenberg, & Desreumaux, ) and prefers temperatures below 20°C (Castellani, Licandro, Fileman, di Capua, & Grazia Mazzocchi, ), which strengthens the speculation that its occurrence in tropical regions may be based on misidentifications (Nishida, ). A recent finding has also shown that O. similis is a complex of independent lineages with distinct biogeographies linked to climate zones, and not a single cosmopolitan species (Cornils et al., ). Oithona atlantica is also widely distributed and occurs in the temperate and polar oceanic regions of the Atlantic and Pacific Ocean (Cepeda, Blanco‐Bercial, Bucklin, Beron, & Vinas, ; Nishida, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of species show large-scale patterns of genetic diversity associated with latitudinal gradients (e.g., Francisco et al 2014) and among ocean basins, including Eukrohnia hamata (Miyamoto et al 2012), Pleuromama abdominalis , and Oithona similis (Cornils et al 2017). …”
Section: Population Genetic Diversity and Structurementioning
confidence: 99%
“…Results can be interpreted to estimate and understand the age of the lineage in terms of time to coalescence (i.e., the common ancestral gene from which all current copies of the gene are descended), as well as imprints of demographic history on populations and species (Knowles 2009). Among marine zooplankton, mitochondrial markers have been used most regularly to infer demographic history (e.g., Peijnenburg et al 2005;Aarbakke et al 2014;Cornils et al 2017), including marine invasions (Cristescu 2015;Lee 2016;Sherman et al 2016), population expansions and contractions (Edmands 2001), geographic isolation giving rise to speciation events (Lee 2000;Peijnenburg et al 2004;Miyamoto et al 2010), and divergence of genetic lineages following major global climate events (Papadopoulos et al 2005;Blanco-Bercial et al 2011b;Milligan et al 2011). …”
Section: Population Genetic Diversity and Structurementioning
confidence: 99%